Professional boundaries - Elnaem, Mohamed Hassan Abdelaziz; Hamdy, Noha Alaa (Elsevier, 2019)
Professional boundaries in pharmacy practice can be divided into three major sections. The first section comprises professional boundaries in relation to the pharmacist's relationship with patients as a caregiver. It involves a code of ethics that governs the pharmacist-patient interaction and the shared decision-making process. The second section involves professional boundaries with regard to the pharmacist's relationship with other health caregivers from the perspective of interprofessional learning, facilitators, and barriers to collaborative practice. Interprofessional education is a mean of providing early exposure and more elasticity to medical and allied professional relationships. The last section is directed toward underpinning the perceived professional boundaries in the social interactions between students and faculty staff members who are their role models. The promotion of knowledge about professional boundaries, important warning signs, behaviors, and attitudes should be considered as early as in the health-care education of undergraduates. It is the responsibility of educational institutions, management of health-care facilities, and policymakers to exert continuous efforts and initiatives toward maintaining professional boundaries and facilitating the upholding of a professional identity in daily practice.